What a Difference a Grade Makes: Evidence from New York City's Restaurant Grading Policy. (28th July 2019) - Rothbart, Michah W.; Schwartz, Amy Ellen; Calabrese, Thad D.; Papper, Zachary; Mijanovich, Todor; Meltzer, Rachel; Silver, Diana
Abstract: Can governments use grades to induce businesses to improve their compliance with regulations? Does public disclosure of compliance with food safety regulations matter for restaurants? Ultimately, this depends on whether grades matter for the bottom line. Based on 28 months of data on more than 15, 000 restaurants in New York City, this article explores the impact of public restaurant grades on economic activity and public resources using rigorous panel data methods, including fixed‐effects models with controls for underlying food safety compliance. Results show that A grades reduce the probability of restaurant closure and increase revenues while increasing sales taxes remitted and decreasing fines relative to B grades. Conversely, C grades increase the probability of restaurant closure and decrease revenues while decreasing sales taxes remitted relative to B grades. These findings suggest that policy makers can incorporate public information into regulations to more strongly incentivize compliance .